Impact of regionally increased CO2 concentrations in coupled climate simulations - Semmler, Tido; Pithan, Felix; Jung, Thomas (Zenodo, 2020)
This poster has been presented at the General Assembly of the EU project APPLICATE which has taken place in Louvain-la-Neuve, Belgium, from the 20th to 23rd of January, 2020. It is a summary of the paper by the same authors (Semmler et al., 2020: Quantifying two-way influences between the Arctic and mid-latitudes through regionally increased CO2 concentrations in coupled climate simulations, doi: 10.1007/s00382-020-05171-z). One of the main conclusions is: Arctic CO2 forcing shows limited influence on extra-Arctic regions, extra-Arctic CO2 forcing shows strong influence on Arctic including substantial sea ice melting leading to Arctic Amplification.